From glacier retreat to sustainable development: how a climate-resilient water management can contribute to transformative change in mountains - Jonas Geschke; Katharina Michael; Tallulah Gundelach (Frontiers in Ecology and Evolution)
Mountains are particularly affected by climate change, and its impacts on mountains and associated glaciers are increasingly well understood. The changes in downstream water flow regimes have far-reaching impacts on nature and people. Yet, climate change adaptation in mountains is lagging behind. Using the requirements of a climate-resilient water management, we explore ice reservoirs and dams as local climate change adaptation measures, addressing glacier retreat through compensating for the loss of ice storage. Based on this, we identify specific demands to promote sustainable development in mountain regions affected by glacier retreat. While glacier retreat can only be counteracted by limiting global warming, context-specific and effective adaptation to changing mountain environments should address socio-economic challenges as well as safeguarding ecosystem services equally.